Lupus and pulmonary nodules consistent with bronchiolitis obliterans organizing pneumonia induced by carbamazepine in a man - Awatef Kelati (Nasza Dermatologia Online, 2016)
Several drugs have been implicated in the induction of systemic lupus erythematosus (SLE), but there are only some observations of carbamazepine induced SLE since the first case described in 1966, this drug has also been implicated in the induction of other disorders and rarely pulmonary toxicity; but the occurrence of two rare side effects of this drug: the induced SLE and pulmonary nodules consistent with the bronchiolitis obliterans organizing pneumonia in same patient is really unusual and -to our knowledge- the second observation reported in the literature.